Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1016/j.jacc.2007.01.091
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, Randomized, Double-Blind, Placebo-Controlled Study on the Effect of Oral Tolvaptan on Left Ventricular Dilation and Function in Patients With Heart Failure and Systolic Dysfunction

Abstract: In a well-treated population of stable HF patients, there was no significant effect of tolvaptan therapy on LV volumes observed during 1 year of therapy. Nonprespecified natural history data favored therapy with tolvaptan, with a reduction in the combined end point of mortality and heart failure hospitalization observed. (Multicenter, Randomized, Double-Blind, Placebo Controlled, Efficacy Study on the Effects of Tolvaptan on Left Ventricular Dilatation in Congestive Heart Failure Patients; http://clinicaltrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
114
3
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 33 publications
0
114
3
5
Order By: Relevance
“…6) Tolvaptan is a vasopressin type 2 receptor antagonist that is effective in patients with HF. [7][8][9][10][11][12][13][14] Tolvaptan became available in Japan for the treatment of HF in 2010. When sufficient diuresis is not achieved with diuretics such as loop diuretics, tolvaptan is recommended.…”
mentioning
confidence: 99%
“…6) Tolvaptan is a vasopressin type 2 receptor antagonist that is effective in patients with HF. [7][8][9][10][11][12][13][14] Tolvaptan became available in Japan for the treatment of HF in 2010. When sufficient diuresis is not achieved with diuretics such as loop diuretics, tolvaptan is recommended.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] High age and chronic kidney disease are known risk factors of refractoriness to TLV, [10][11][12] whereas preserved function of the renal collecting duct, which is confirmed by a higher level of urine aquaporin-2 (U-AQP2) relative to plasma AVP (P-AVP), is a predictor of responses to TLV. 13) Responders seem to experience not only an improved clinical course but also better prognosis during TLV treatment compared with those not receiving TLV.…”
mentioning
confidence: 99%
“…15) However, it has been also demonstrated that administration of tolvaptan was not associated with increases in systolic vascular resistance nor progression of left ventricular remodeling. 11,16) Considering these results, increases in AVP after administration of tolvaptan may be too trivial to significantly stimulate V1a receptors. The preserved blood pressure observed in our study may have resulted from mobilization of free water from the third space into the vascular space due to increased serum osmolality.…”
Section: Discussionmentioning
confidence: 99%